Does energy innovation play a role in achieving sustainable development goals in BRICS countries?. Issue 15 (3rd July 2022) - Baloch, Muhammad Awais; Danish; Qiu, Yiting
ABSTRACT: It is widely discussed that greenhouse gases (GHGs) are the main culprit behind global warming. The conventional energy sources (oil, coal, and gas) mainly realize GHGs in the atmosphere. Due to this, the world's countries are switching towards clean energy sources and investing more in projects related to innovation in the energy sector. Thus, this study investigates the role of energy innovation in combating GHGs emissions by taking the environmental Kuznets curve for BRICS economies. The FMOLS and DOLS estimators are employed throughout 1996-2016. The findings documented that energy innovation plays an important role in mitigating GHGs emissions. Moreover, the result strongly approves the EKC hypothesis for BRICS countries in the significance of energy innovation. Finally, it is recommended that expanding the public budget in energy R&D expenditures can help to reduce GHG emissions and promote sustainable growth in BRICS countries. GRAPHICAL ABSTRACT: UF0001